Absence of LEDGF/p75 Expression in Astrocytes May Affect HIV-1 Integration Efficiency - Yoder, K. E. (Mol Gen Microbiol Virol, 2019)
In spite of effective anti-retroviral therapy, HIV-1 infection may still lead to neurological impairment in patients. The underlying mechanism of neurodegeneration remains mysterious. HIV-1 does not infect neurons, but does infect microglia cells in the brain. It is controversial whether HIV-1 productively infects astrocytes, an abundant glial cell type in the brain. Thirty years of investigation have led to conflicting reports concerning the entry, infection, and production of progeny virions from astrocytes. New models from studies in primary human fetal astrocytes suggest phagocytosis of HIV-1 with little productive infection. The retroviral life cycle requires integration of the viral genome to the host genome. The host protein LEDGF/p75 is required for efficient HIV-1 integration. In the absence of LEDGF/p75, HIV-1 integration and infection efficiency is reduced ten fold. Differentiated astrocytes do not appear to express LEDGF/p75, which suggests these cells are disabled for efficient integration. Phagocytosis of HIV-1 virions and the lack of LEDGF/p75 expression in astrocytes suggest that this cell type is not efficiently infected in vivo.